Rol de TGF-b1 en la fibrosis de la piel inducida por radioterapia en cáncer de cabeza y cuello - Arroyo D., Michelle; Nazar S., Rodolfo (Revista Hospital Clínico Universidad de Chile, 2011)
Introduction: radiotherapy (RT) is a major part of the treatment of head and neck cancer, but it can produce skin fibrosis and other complications. Fibrosis is produced by an increase of the fibroblasts (FB) and extra-cellular matrix proteins. TGF-b is one of the several factors implied in FB proliferation, and it is the most important element in the development of radiation fibrosis. Temporality of radiation fibrosis: there are two successive stages in the fibrosis development. An actively inflammatory with high TGF-b1 secretion one, and a second stage characterized by hypo-cellularity and low TGF-b1 secretion. TGF-b: an induction of TGF-b1 and its mRNA in animals skin during the first hours post irradiation have been demonstrated. By studying surgical skin biopsies post RT and fibrotic tissues post exposure to radiation, it was observed over-expression of TGF-b1. Discussion: there is a lot of new knowledge of the molecular process implied in radiation skin fibrosis. A future goal is to potentiate this information to improve our tools in prevention and treatment of fibrosis in patients that undergone RT because of cancer.